Design and Implementation of Wiki Content Transformations and Refactorings - Dohrn, Hannes; Riehle, Dirk (Proceedings of the 9th International Symposium on Open Collaboration, 2013)
The organic growth of wikis requires constant attention by contributors who are willing to patrol the wiki and improve its content structure. However, most wikis still only oer textual editing and even wikis which oer WYSIWYG editing do not assist the user in restructuring the wiki. Therefore, "gardening" a wiki is a tedious and error-prone task. One of the main obstacles to assisted restructuring of wikis is the underlying content model which prohibits automatic transformations of the content. Most wikis use either a purely textual representation of content or rely on the representational HTML format. To allow rigorous definitions of transformations we use and extend a Wiki Object Model. With theWiki Object Model installed we present a catalog of transformations and refactorings that helps users to easily and consistently evolve the content and structure of a wiki. Furthermore we propose XSLT as language for transformation specification and provide working examples of selected transformations to demonstrate that theWiki Object Model and the transformation framework are well designed. We believe that our contribution significantly simplifies wiki "gardening" by introducing the means of eortless restructuring of articles and groups of articles. It furthermore provides an easily extensible foundation for wiki content transformations. Categories and Subject Descriptors H.4 [Information Systems]: Information Systems Applications; I.7 [Computing Methodologies]: Document and Text Processing; D.2 [Software]: Software Engineering General Terms Design, Languages. Copyright 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.popsos.design
Keywords: Wiki; Wiki Markup; WM; Transformation; Refactoring; XML; XSLT; Sweble